Prevalence of Sexual Assault Victimization Among College Men, Aged 18–24: A Review. Issue 6 (2nd November 2017) - Forsman, R. Lane
ABSTRACT: Purpose: The current review provides summary and evaluation of prevalence data for the sexual victimization of college men ages 18 – 24. Methods: Potential studies were selected by searching electronic bibliographic databases. Studies were initially selected for inclusion if they (1) assessed prevalence rates of sexual victimization on college campuses and (2) were published in a scholarly journal (3) in the English language. Utilizing this strategy, 3, 973 studies were initially identified, of which 5 underwent complete review. Results: All 5 studies returned results for sexual victimization of men on college campuses. However, identified prevalence data varies widely from 3.2% – 28.7% of the males surveyed. When incapacitation as a form of victimization was included in the study, college men as a whole appear to be most vulnerable to this form of sexual violence, though sexual minority males may have more heterogeneous experiences of victimization. Conclusions: Conceptualization of sexual victimization and wording of items attempting to assess prevalence rates likely lead to underestimation of true prevalence. Even with an incomplete understanding of prevalence, results suggest that continuing to assess prevalence may not be the most pressing need at this time. Research into the kinds of victimization college men face as well as education, prevention, and intervention within these areas may likely do more to positively advance the knowledge base.